Thermal and Solutal Mixed Marangoni Boundary Layers with Suction or Injection Effects - Ahmad, Noraini; Awang Kechil, Seripah; Mohd Basir, Norma (Journal of Science and Technology, 2012)
A steady two-dimensional Marangoni boundary-layer flow over a permeable flat surface is considered. The surface tension is assumed to vary linearly with temperature and solute concentration. The transformed similarity boundary layer equations are obtained and solved numerically by Runge-Kutta-Fehlberg with shooting technique. The Marangoni and external pressure gradient effects that generated in boundary layer flow are assessed. As the suction/ injection parameter increases from injection to suction, the velocity, temperature and concentration boundary layers thickness decrease but injection increases them. The thermosolutal surface tension ratio increases the velocity boundary thickness but decreases the temperature and concentration boundary layers.